2012
DOI: 10.4209/aaqr.2012.05.0138
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Black Carbon in PM2.5 at an Urban Site at Dhaka, Bangladesh

Abstract: The results from 1-year of measurements of PM 2.5 , organic carbon (OC) and black carbon (BC) concentrations are presented for an urban traffic-influenced site, the Farm Gate in Dhaka, Bangladesh. The measurements were based on sampling using two Air Metrics simultaneously operating samplers. The concentrations of OC and BC concentrations in PM 2.5 varied from 5-96 μg/m 3 and 4-48 μg/m 3 , respectively. The concentrations of PM 2.5 varied from 11-328 μg/m 3 . The annual particulate organic matter (POM) account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 41 publications
0
18
1
Order By: Relevance
“…Average seasonal concentrations of OC obtained in this study are comparable to those reported for respective seasons for other two Indian cities, Kanpur and Hisar (Ram and Sarin 2010a, b); however EC concentration obtained for Pune and Hyderabad are higher than those for Kanpur and Hisar. On the other hand, OC and EC concentrations at some of the highly urbanized Asian cities such as Dhaka in Bangladesh and Beijing in China (Begum et al 2012;Dan et al 2004) are higher than those obtained in the present study. There are some other developed areas in the Asia such as Hong Kong (China), Bangkok (Thailand), Tokyo and Saitama (Japan) where carbonaceous particles concentration has been reported either to be comparable to or less (Cao et al 2007;Kim et al 2011;Sahu et al 2011) than those obtained in the present study.…”
Section: Variation At Hyderabadcontrasting
confidence: 85%
“…Average seasonal concentrations of OC obtained in this study are comparable to those reported for respective seasons for other two Indian cities, Kanpur and Hisar (Ram and Sarin 2010a, b); however EC concentration obtained for Pune and Hyderabad are higher than those for Kanpur and Hisar. On the other hand, OC and EC concentrations at some of the highly urbanized Asian cities such as Dhaka in Bangladesh and Beijing in China (Begum et al 2012;Dan et al 2004) are higher than those obtained in the present study. There are some other developed areas in the Asia such as Hong Kong (China), Bangkok (Thailand), Tokyo and Saitama (Japan) where carbonaceous particles concentration has been reported either to be comparable to or less (Cao et al 2007;Kim et al 2011;Sahu et al 2011) than those obtained in the present study.…”
Section: Variation At Hyderabadcontrasting
confidence: 85%
“…Therefore, the presence of Si particles in our study is from some likely combination of transported windblown soil particles, re-suspended dust from vehicular traffic or construction, and from industrial combustion (Houghton et al , 2001; Herman et al , 1997). Since particulate C offers attractive adsorption sites for various volatile compounds, its higher amount can promote deleterious health effects (Begum et al , 2012; Pipal et al , 2014). …”
Section: Resultsmentioning
confidence: 99%
“…S2(b), reflecting increased space heating use with the onset of colder periods. Maximum BC was also observed from November to February at urban locations in the USA , Europe (Saha and Despiau, 2009) India and Bangladesh (Baxla et al, 2009;Begum et al, 2012;Swamy et al, 2012). However in Hong Kong maximum BC was found from July to September (Cheng et al, 2012) indicating sources other than nearby traffic was impacting the site during the summer period.…”
Section: Monthly Patternmentioning
confidence: 94%